Clinical Response of Enhanced External Counter Pulsation (EECP) Among Bangladeshi Ischemic Heart Disease Patients (University Heart Journal, 2012)
EECP is used to stabilize the coronary circulation in patients with severe coronary artery disease when maximal medical therapy and/or invasive procedures have proven inadequate. This prospective observational study was done for a period of 12 months. 40 patients with angina and angiographically proven coronary artery disease, who met the inclusion and exclusion criteria was enrolled in this study. Among 40 enrolled patients 30 (70%) patients completed their treatment. All the patients were in between 42 to 80 years age group. All patients required sublingual nitrate before started EECP treatment. But after completion of treatment, 75% patient required no nitrates. Who completed full course, 100% were improved their angina symptoms from class II, III, IV to class I. Overall 80% patients improved their quality of life. Those completed full course of treatment 100% patients improved their quality of life. EECP Heart therapy is now world-wide accepted alternative treatment option for those patients, who are not fit for surgery or any kind of interventional procedure and those developed heart failure. DOI: http://dx.doi.org/10.3329/uhj.v7i1.10205 UHJ 2011; 7(1): 19-22